Physiotherapy: an active, transformational, and authentic career choice. (4th May 2021) - Harman, Katherine; Sim, Meaghan; LeBrun, Jeff; Almost, Joan; Andrews, Cynthia; Davies, Harriet; Khalili, Hossein; Sutton, Evelyn; Price, Sheri
ABSTRACT: Background : This paper arises from a larger study exploring early professional socialization across five professions: physiotherapy, nursing; dentistry; pharmacy; and medicine. Purpose : To explore the process of physiotherapy student professional identity development and the evolution of expectations and views of interprofessional practice in the first year of their program. Methods : One-on-one interviews at three time points: after being accepted into the physiotherapy program and before classes began (T1; n = 12); after term one (T2; n=9) and on completion of year one (T3; n = 7). Analyses employed narrative methodology, guided by anticipatory socialization and professional identity theories. Results : At T1, participants described their path towards physiotherapy, indicating career satisfaction as the core of their choice. Expectations of practice aligned with the normative social positioning of the profession. T2 and T3 interviews revealed that their pre-entry conceptualization of practice was both challenged and positively reinforced, leading them either to being satisfied with, or questioning their choice. Clinical placements created the most meaningful opportunities to understand their roles both as individual professionals and members of a collaborative team. Conclusion : Findings revealed the complex process of professional socialization in physiotherapy students with implications for admissions and formal and IPE curricula.